Systematic review of prostate cancer risk and association with consumption of fish and fish‐oils: analysis of 495, 321 participants. Issue 1 (11th December 2014) - Lovegrove, C.; Ahmed, K.; Challacombe, B.; Khan, M. S.; Popert, R.; Dasgupta, P.
Summary Introduction Fish‐oils have a potential role in inflammation, carcinogenesis inhibition and favourable cancer outcomes. There has been increasing interest in the relationship of diet with cancer incidence and mortality, especially for eicosapantaenoic acid (EPA) and docosahexaenoic acid (DHA). This systematic‐analysis of the literature aims to review evidence for the roles of dietary‐fish and fish‐oil intake in prostate‐cancer (PC) risk, aggressiveness and mortality. Methods A systematic‐review, following PRISMA guidelines was conducted. PubMed, MEDLINE and Embase were searched to explore PC‐risk, aggressiveness and mortality associated with dietary‐fish and fish‐oil intake. 37 studies were selected. Results A total of 495, 321 (37‐studies) participants were investigated. These revealed various relationships regarding PC‐risk (n = 31), aggressiveness (n = 8) and mortality (n = 3). Overall, 10 studies considering PC‐risk found significant inverse trends with fish and fish‐oil intake. One found a dose–response relationship whereas greater intake of long‐chain‐polyunsaturated fatty acids increased risk of PC when considering crude odds‐ratios [OR: 1.36 (95% CI: 0.99–1.86); p = 0.014]. Three studies addressing aggressiveness identified significant positive relationships with reduced risk of aggressive cancer when considering the greatest intake of total fish [OR 0.56 (95% CI 0.37–0.86)], dark fish and shellfish‐meat (p < 0.0001), EPA (p = 0.03) and DHA (p = 0.04). Three studies investigating fish consumption and PC‐mortality identified a significantly reduced risk. Multivariate‐OR (95% CI) were 0.9 (0.6–1.7), 0.12 (0.05–0.32) and 0.52 (0.30–0.91) at highest fish intakes. Conclusions Fish and fish‐oil do not show consistent roles in reducing PC incidence, aggressiveness and mortality. Results suggest that the specific fish type and the fish‐oil ratio must be considered. Findings suggest the need for large intervention randomised placebo‐controlled trials.